HERMENEUTIKA ALQURAN MENURUT MOHAMMED ARKOUN - Samdani, Samdani (Fakultas Ushuluddin dan Humaniora IAIN Antasari, 2014)
Muslims since the beginning of Islam has noticed how the interpretation and rules, methodology and matters relatingto the interpretation of the application of the Koran. This can be seen in the literature that still exists today. Inaddition to a variety of scientific disciplines that developed in the history of Islam and the Muslims, the Qurâanicstudies is a discipline that must be learned to be applied in interpreting the Qurâan. But after entering the latestdevelopments, the study of the Koran interacted with some ideas in the West. Some orientalists were concerned aboutthe study of the Qurâan began to incorporate some western methodologies, including hermeneutics. Parties orientaliswas distracting so great to change thinking in Indonesia that have been started since the early 1980s. The works ofMuslim scientists who follow in the footsteps of orientalists such as Hasan Hanafi, Mohamed Arkoun, Nasr Hamid,Fazlurrahman, Muhammad Shahrur and others, enough to attract interest among Muslim scientists. This paperfocused on one Mohamed Arkoun among the many Muslim thinkers who had contributed in the methodology ofinterpretation of the Koran.